Edible-based and non-toxic corrosion inhibitor / Hazlina Husin, Md. Amin Hashim and Izni Mariah Ibrahim - Husin, Hazlina; Hashim, Md. Amin; Ibrahim, Izni Mariah (Research Innovation Business Unit, 2014)
Problems attributed to the deterioration of metal by chemical reaction with the environment are called corrosion. Corrosion reaction is an electrochemical process in nature which consists of an anodic site where dissolution of the metal takes effect leading to the release of electrons; and a cathodic site where the electrons react with some reducible components of the electrolyte. Corrosion costs billions of dollars every year and in the middle of 2013 this cost reached more than $2 trillion or 3-5% of Gross Domestic Product (GDP) in the United States. Besides that, corrosion can also have far reaching damages and environmental consequences. Some oil companies had their pipeline ruptured due to corrosion and oil spillages are experienced creating environmental pollution. Macpherson (2013) reported that, the pipeline leak that occurred in Tioga, North Dakota on September 2013 is due to severe internal corrosion. The effects of pipe leakage is the occurrence of oil spills and it took about 3 years to clean up all the spilled crude oil. Metal corrosion can be prevented by employing cathodic protection, anodic protection, coating, alloying and chemical inhibitors. Among the prevention methods, the use of chemical inhibitor is the most practical and economical. This invention is a chemical inhibitor formulated using mainly malic acid compounds. These malic acid compounds have been extracted from biomass resources, which are the banana peels and the banana pseudosem. According to previous studies, both banana peels and banana pseudosem contain malic acid compounds. During ripening, banana peels were found to contain up to 0.66 g of malic acid per 100 g. Unlike the common commercial chemical inhibitors which were manufactured from petroleum derivatives, malic acid compounds are categorized as edible organic acids (with food standard, 1993) and are considered to be non-toxic. Prior to a more stringent environment law for oil and gas industries, this invention of an edible-based and non-toxic corrosion inhibitor is very potential to be applied on steel bar of oil and gas platforms and facilities equipment. Banana (Musaceae) is one of the world’s most important fruit crops that are widely cultivated in tropical countries for its valuable applications in food industry. Alternatively, its readily available biomass waste such as the banana peels and banana pesudosem used in this invention is an excellent source for a highly valuable chemical inhibitor. Manufacturing this specially formulated corrosion inhibitor can prevents ultimate loss of huge amount of untapped biomass, can reduce significantly the agricultural waste and solve environmental issues. This invention has undergone the standard corrosion inhibition test and has been proven to have 100% inhibition corrosion efficiency. The correlation of the molecular attribute of the malic acid compounds upon the surface of the metal protected and its efficiency have been presented in several journal articles authored by the inventor. Detailed explanation can be referred to in journal articles. Through many years of research, the inventor convinced that the malic acid compounds which have been extracted from agricultural waste have the efficiency equivalent to the costly, commercial chemical inhibitors.